Lean Manufacturing for Improvement and Productivity in the Supply Chain of a Pisco Company - Landa Romero, Esteban Patricio (2024)
Maintaining proper administration and management within supply chain processes ensures the competitiveness and sustainability of the company. This study aims to propose an improvement in the supply chain of a pisco company through the implementation of Lean Manufacturing tools. The model was designed and validated, subdivided into four components that specify and detail the sequence of the proposal's improvement (analysis and measurement, solution design, application, and evaluation of results). Among the main findings is a 40% improvement in the productivity rates of the packaging process, along with a reduction in downtime during the grape extrusion process (with a saving of approximately 12 minutes per breakdown). Consequently, there was an increase in the mean time between failures (MTBF) by 54.87%, equivalent to an interval of three days with seven hours of work without any faults. Finally, there was an increase in the efficiency of the use of the main resource, "uvina grapes," by 33%, signifying high raw material performance during the extrusion process. This study facilitates the transition to a continuous improvement environment, aiming to stimulate future research to contribute to process improvement in small and medium-sized enterprises (SMEs). The expectation is that these companies can develop tools to optimize their main bottlenecks, achieving improvements in their operations in terms of resources and time.